Hubungan Kesiapan dan Kreativitas Belajar terhadap Prestasi Belajar Siswa pada Mata Pelajaran PAI Di SMAN 3 Tambusai Utara - Anam Besari; M. Irfan Luthfi Rangkuti; Nur Khozin; Diana Diana; Fatoni Achmad; Ary Asy’ari (CV. Creative Tugu Pena, 2026)
This study aims to examine the relationship between students’ learning readiness and learning creativity and their academic achievement in Islamic Religious Education (PAI) at SMA Negeri 3 Tambusai Utara. This field study employed a quantitative approach. The study involved the entire student population of SMA Negeri 3 Tambusai Utara, consisting of 204 students. Data were collected through questionnaires and documentation. The data were analyzed using correlation coefficient tests to determine the relationships among the variables. The findings indicate that students’ learning readiness has a positive and significant relationship with their academic achievement in Islamic Religious Education. This is evidenced by a Sig. (2-tailed) value of 0.000, which is lower than 0.05. Similarly, students’ learning creativity demonstrates a positive and significant relationship with their academic achievement, as indicated by a Sig. (2-tailed) value of 0.000 < 0.05. Furthermore, the combined variables of learning readiness and learning creativity are positively and significantly related to students’ academic achievement in Islamic Religious Education. This finding is supported by a Sig. F Change value of 0.000 < 0.05. Therefore, the results confirm that both learning readiness and learning creativity are significantly associated with students’ academic achievement in Islamic Religious Education at SMA Negeri 3 Tambusai Utara.